Mindfulness‐based stress reduction training yields improvements in well‐being and rates of perceived nursing errors among hospital nurses. (8th July 2018) - Daigle, Stephanie; Talbot, France; French, Douglas J.
Abstract: Introduction: This pilot study aims to further document mindfulness‐based stress reduction (MBSR)'s effect on well‐being while exploring its impact on errors among hospital nurses. Background: The concept of mindfulness has been found to be highly relevant to holistic nursing practices but remains understudied and underused. Preliminary evidence suggests that MBSR can reduce stress among nurses. As stress and mental processes such as inattention are potential sources of error, MBSR may also help to improve patient safety. Reducing errors is of significant relevance in healthcare settings. Design: A randomized controlled trial with a matched pair design was conducted. Methods: Seventy Registered Nurses and licensed practical nurses were randomized to MBSR ( N =  37) or a waitlist control condition ( N =  33). Results: Intention‐to‐treat ANCOVAs revealed that MBSR produced significant improvements in distress. High levels of treatment satisfaction were reported by a majority of participants. Of the nurses who reported that errors had been a problem for them (28.6%), a perceived improvement was noticed by over a third (37.5%) at 3 months post‐treatment. Conclusion: These initial findings suggest that the benefits of MBSR may extend to nursing errors. Abstract : 摘要: 简介: 该初步研究旨在进一步记录正念减压(MBSR)对医院护士幸福感的影响, 同时探讨其对医院护士出现错误的影响。 背景: 已经发现正念概念与整体护理实践高度相关, 但仍未得到充分研究, 也未充分利用。初步证据表明, 正念减压可以减轻护士的压力。由于压力和心理过程(如注意力不集中)是潜在的错误来源, 正念减压也可能有助于提高患者安全性。减少错误对于医疗保健来说具有重要意义。 设计: 进行的随机对照试验采用了配对设计。 方法: 将70名经注册的护士和执业护士随机分配到正念减压组( N = 37 )或候补对照组( N = 33 )。 结果: 意向治疗协方差分析结果显示正念减压在遭遇困境时有显著的改善效果。大多数参与者表示对疗效的满意度较高。在正念减压治疗后的第三个月, 对于表示犯错误对他们来说是个问题的护士(28.6%)中, 超过三分之一(37.5%)的护士感觉到有所改善。 结论: 这些初步研究结果表明, 正念减压的益处可能有助于降低护理错误率。: